Caracterização hidroquímica dos sistemas aquíferos Serra Geral e Guarani da sub-bacia do Rio Pardo e municípios adjacentes, no sudoeste do estado de São Paulo - Bodelão, Thomás Gerdulo [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The main purpose of this work is to evaluate the chemical composition of the groundwaters from Guarani Aquifer System and Serra Geral Aquifer System in the Rio Pardo basin, located at the southwestern of São Paulo state. To the hydrochemical characterization, physicalchemical analyses from 32 sampled wells were used. These results were plotted in Piper diagrams allowing the classification of groundwater as calcium or calcium-magnesium bicarbonate type and sodium bicarbonate type for both aquifer systems. Distribution of hydrochemical facies over the study area was obtained using Stiff diagrams. The groundwater can be classified, representing in this sequence its hydrochemical evolution. The recognized mechanisms responsible for groundwater evolution are dissolution of minerals magnesium, such as olivine, present in the basalt, dissolution of feldspars and removal of the carbonate cement of the sandstones mineral framework. Ionic exchange may represent an important processes in the groundwater evolution, responsible for the increase in the sodium concentration and decrease of calcium

O presente trabalho teve por objetivo a caracterização hidroquímica das águas subterrâneas dos sistemas aquíferos Guarani e Serra Geral, na sub-bacia do rio Pardo, no sudoeste do estado de São Paulo. Para tanto foram realizadas análises físico-químicas das águas coletadas em 32 poços. Os resultados das análises químicas foram plotados em diagramas de Piper, permitindo sua classificação em: bicarbonatadas cálcicas, cálcio-magnesianas e bicarbonatadas sódicas em ambos os sistemas. A plotagem em diagramas de Stiff permitiu a visualização da composição hidroquímica em área. Os mecanismos envolvidos na evolução hidroquímica dessas águas são: dissolução de minerais magnesianos, como a olivina presente no basalto, e dissolução de feldspatos e remoção do cimento carbonático do arcabouço mineral dos arenitos. Além dessas reações químicas, a troca iônica parece ter sido um processo efetivo na evolução dessas águas, responsável pelo aumento nas concentrações de sódio e diminuição nas concentrações de cálcio
Keywords: Quimica da agua; Águas subterrâneas; Hidrogeologia; Geoquimica; Aquífero Guarani; Paranapanema, Rio, Bacia (SP e PR); Pardo, Rio, Bacia (MG, SP); Water chemistry; Hydrogeology; Groundwater; Geochemistry